REGIONAL POPULATIONS AND MIGRATION OF MOOSE IN NORTHERN YAKUTIA, RUSSIA - Safronov, Valeriy M (Lakehead University, 2009)
Following an overall population decline of moose (Alces alces) after the 1970s, extensive aerial and ground surveys conducted since 1985 indicated that there were 7 distinct populations in northern Yakutia. They are isolated geographically by mountain ridges and major rivers, and are named the Leno-Olenek, Predverkhoyansk, Yana, Chondon, Momo-Selenyakh, Indigirka, and Kolyma populations. Although most occupy forest habitat associated with major rivers, some are migratory (40-200 km) moving both N-S and E-W, and certain populations overlap on winter range. Population densities generally range from 1-2 moose/10 km2, with higher and lower local densities. The northernmost Chondon population is unique by occupying sub-tundra forests and ridges. Because protective regulations did not produce measurable population recovery and were abandoned in 2004, management strategies must be adopted to address the ecological differences of these separate populations. Effective moose management in Yakutia will require further identification of range and habitat use, habitat structure and availability, and population estimates and dynamics of regional populations.